Morfologia e germinação de sementes de jambu (Acmella oleracea L. R. K. Jansen) - Sousa, Erivanessa Costa (Universidade Federal Rural do Semi-Árido, 2018)
Jambu (Acmella oleracea L. R. K. Jansen) is an unconventional herbaceous species, used for medicinal and food purposes, with little information related to the agronomic aspects, mainly in relation to seed technology. The objective was to evaluate the morphological aspects of seedlings and the germination of jambu seeds under different temperatures and water deficit. For that, three experiments were developed in the Laboratory of Seed Analysis (LAS) of the Federal Rural University of the Semi-Arid, Mossoró, RN. In the first experiment, samples of 100 seeds from two sources (Belém and Castanhal, PA) were used, where seed biometry (length, width and thickness), weight of one thousand seeds, number of seeds g-1 and content of water. Also, the descriptions of the external structures of the seeds and seedlings and the monitoring of the imbibition curve were realized. In the second experiment, the seeds of the two sources were placed to germinate at constant temperatures of 20, 25, 30 and 35 ° C and alternating between 20-30 and 25-35 ° C, under a photoperiod of 12 h light and 12 h dark. The evaluated characteristics were: germination, germination speed index, seedling length and dry mass. In the third experiment, the seeds of the two sources were placed on a substrate moistened with solutions of PEG 6000 and mannitol at the osmotic potentials of 0,0; -0.2; -0.4; -0.6 and -0.8 MPa. Germination, germination speed index, seedling length and dry mass were evaluated. The experimental design was a completely randomized design, with four replications for both experiments. The germination of jambu seeds is of the epigene type, with the seedling being phanerocotonon, with foliaceous cotyledons. The radicle protrusion starts from the first day after sowing and the emergence of seedlings with definite essential structures occurs from the fourth day. It was verified that the germination test of the jambu can be conducted under constant temperatures of 25 and 30 ° C and alternating between 20-30 ° C. The decrease in water potential impaired the analyzed characteristics, with a maximum tolerance level of -0.2 MPa in PEG and osmotic potentials equal to or less than -0.6 MPa in mannitol
Morphology and germination of jambu seeds (Acmella oleracea L. R. Jansen)
Keywords: Acmella oleracea; Asteraceae; Morfologia; Temperatura; Déficit hídrico; Acmella oleracea; Asteraceae; Morphology.; Temperature; Water deficit; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA